On degenerate p(x)-Laplace equations involving critical growth with two parameters. (February 2016) - Ho, Ky; Sim, Inbo
Abstract: After establishing a concentration-compactness principle for weighted variable exponent spaces, we show the existence of a nonnegative solution and infinitely many solutions for degenerate p ( x ) -Laplace equations involving critical growth with two parameters using various techniques in Calculus of Variations.